Anticorrosive flame-retardant composite insulation board
Patent Information
- Application Number
- CN202611160702.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]为了克服上述的技术问题,本发明的目的在于提供一种防腐阻燃复合绝缘板,解决了现有的环氧树脂基绝缘板的阻燃性能和防腐性能不佳,极易出现腐蚀影响性能下降,严重影响其电气绝缘性,并且易于点燃甚至燃烧蔓延,严重影响其防火安全性,无法满足高端装备对绝缘材料综合性能的严苛需求的问题
本发明的一种防腐阻燃复合绝缘板,通过将环氧树脂、固化剂、促进剂、丙酮、磷氮氟硅化合物、改性水滑石、抗氧剂、脱泡剂以及分散剂加入知混合机中混合均匀,得到板材基料,将板材基料倒入至模具中,之后静置放置、固化,得到防腐阻燃复合绝缘板;该复合绝缘板以环氧树脂为主要原料,向其中添加磷氮氟硅化合物、改性水滑石能够在复合绝缘板内部形成阻燃网络,显著提升复合绝缘板的阻燃性能,大幅提升复合绝缘板的安全性,而且该阻燃网络还具有优异的防腐性能,使其难以被腐蚀介质侵蚀,使其在易腐蚀环境中长时间保持良好的性能,大幅提升复合绝缘板的可靠性,从而使得复合绝缘板兼具良好的机械性能、阻燃性能和防腐性能,满足了其在高温和腐蚀环境中的长期使用的要求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of insulating boards, and more specifically to a corrosion-resistant and flame-retardant composite insulating board. Background Technology
[0002] Composite insulation boards are key basic insulation components in power electrical and electronic equipment. With the rapid development of new energy storage power stations, high-voltage direct current transmission, and marine engineering equipment, extremely stringent requirements have been placed on the performance of insulation boards. Although traditional epoxy resin-based insulation boards possess basic electrical insulation properties, they are highly susceptible to corrosion and performance degradation under harsh environments such as high humidity, salt spray, high temperature, and electric arc, severely affecting their electrical insulation properties. Furthermore, they are easily ignited and can even spread fire, seriously impacting their fire safety and failing to meet the stringent requirements of high-end equipment for the comprehensive performance of insulation materials.
[0003] Therefore, developing a corrosion-resistant and flame-retardant composite insulation board is of great practical significance. Summary of the Invention
[0004] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a corrosion-resistant and flame-retardant composite insulation board, which solves the problems that existing epoxy resin-based insulation boards have poor flame-retardant and corrosion-resistant properties, are prone to corrosion that affects their performance, seriously affect their electrical insulation, and are easy to ignite and even spread, seriously affecting their fire safety and failing to meet the stringent requirements of high-end equipment for the comprehensive performance of insulation materials.
[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a corrosion-resistant and flame-retardant composite insulation board, comprising the following components in parts by weight: The composition includes 100-110 parts epoxy resin, 80-85 parts curing agent, 3-5 parts accelerator, 20-22 parts acetone, 1-7 parts phosphorus, nitrogen, fluorine and silicon compounds, 7-15 parts modified hydrotalcite, 0.7-0.9 parts antioxidant, 0.3-0.5 parts defoamer, and 3-6 parts dispersant. The phosphorus, nitrogen, fluorine, and silicon compound is prepared by the following steps: Step a1: 2,2-bis(4-aminophenyl)hexafluoropropane, methyl p-formylbenzoate, and N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred for 10-20 min at a temperature of 20-25℃ and a stirring rate of 200-300 r / min. The temperature was then raised to 80-90℃ and the mixture was stirred for 6-8 h. DOPO was then added and the mixture was stirred for another 8-10 h. After the reaction was completed, the product was cooled to room temperature. The solvent was then removed by rotary evaporation. The product was then poured into distilled water and vacuum filtered. The filter cake was placed in a vacuum drying oven and dried for 3-4 h at a temperature of 60-70℃ to obtain DOPO-ester-based fluorinated compounds. Step a2: Add DOPO-ester-based fluorinated compound and tetrahydrofuran to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection and stir for 20-30 min at 20-25℃ and 200-300 r / min. Then add potassium hydroxide solution and continue stirring at 60-65℃ for 20-25 h. After the reaction is complete, cool the reaction product to room temperature, remove the solvent by rotary evaporation, pour into hydrochloric acid solution, and then filter under vacuum. Wash the filter cake 2-3 times with distilled water and then place it in a vacuum drying oven at 50-60℃ for 3-4 h to obtain DOPO-carboxyl-based fluorinated compound. Step a3: Add DOPO-carboxylated fluorinated compound, 1-hydroxybenzotriazole and dimethyl sulfoxide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 20-25℃ and 200-300 r / min for 20-30 min. Then add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and triphenylsilanol and continue stirring for 30-50 min. Then raise the temperature to 110-120℃ and continue stirring for 20-25 h. After the reaction is complete, cool the reaction product to room temperature and pour it into distilled water. Then filter under vacuum and wash the filter cake 2-3 times with ethanol. Then place it in a vacuum drying oven and dry at 70-80℃ for 3-4 h to obtain phosphorus, nitrogen, fluorine and silicon compound.
[0006] In a preferred embodiment of the present invention, the ratio of 2,2-bis(4-aminophenyl)hexafluoropropane, methyl p-formylbenzoate, N,N-dimethylformamide and DOPO in step a1 is 10 mmol: 20 mmol: 70-80 mL: 20 mmol.
[0007] In a preferred embodiment of the present invention, the ratio of the amount of DOPO-ester fluorinated compound, tetrahydrofuran and potassium hydroxide solution used in step a2 is 10 mmol: 20-25 mL: 30-35 mL.
[0008] In a preferred embodiment of the present invention, the molar concentration of the potassium hydroxide solution in step a2 is 1-1.2 mol / L; and the molar concentration of the hydrochloric acid solution is 0.03-0.05 mol / L.
[0009] In a preferred embodiment of the present invention, the ratio of the amount of DOPO-carboxylated fluorinated compound, 1-hydroxybenzotriazole, dimethyl sulfoxide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and triphenylsilanol in step a3 is 10 mmol: 0.8-1.2 g: 180-200 mL: 10-12 mmol: 28-30 mmol.
[0010] In a preferred embodiment of the present invention, the modified hydrotalcite is prepared by the following steps: Hydrotalcite, heptadecafluorodecyltriethoxysilane, ethanol, and deionized water were added to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred for 20-30 minutes at a temperature of 20-25℃ and a stirring rate of 200-300 r / min. The pH was then adjusted to 8.5-9.5 with ammonia water, and the temperature was raised to 70-80℃ and the reaction was continued for 4-6 hours with stirring. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The filter cake was washed 2-3 times with distilled water and then placed in a vacuum drying oven and dried at a temperature of 50-60℃ for 2-3 hours to obtain modified hydrotalcite.
[0011] In a preferred embodiment of the present invention, the ratio of the amount of hydrotalcite, heptadecafluorodecyltriethoxysilane, ethanol and deionized water is 2g:1.1-3.7g:70-75mL:10-12mL.
[0012] In a preferred embodiment of the present invention, the average particle size of the hydrotalcite is 300 mesh; and the mass fraction of the ammonia water is 15-20%.
[0013] In a preferred embodiment of the present invention, the method for preparing the corrosion-resistant and flame-retardant composite insulation board includes the following steps: Step 1: Weigh out 100-110 parts of epoxy resin, 80-85 parts of curing agent, 3-5 parts of accelerator, 20-22 parts of acetone, 1-7 parts of phosphorus, nitrogen, fluorine and silicon compounds, 7-15 parts of modified hydrotalcite, 0.7-0.9 parts of antioxidant, 0.3-0.5 parts of defoamer and 3-6 parts of dispersant according to the weight ratio, and set aside. Step 2: Add epoxy resin, curing agent, accelerator, acetone, phosphorus, nitrogen, fluorine and silicon compounds, modified hydrotalcite, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step 3: Pour the board base material into the mold, let it stand for 1-2 hours, then place it in a vacuum drying oven and cure it at 50-60℃ for 1-2 hours, then raise the temperature to 100-110℃ and cure it for 2-3 hours, then raise the temperature to 130-140℃ and cure it for 1-2 hours to obtain the corrosion-resistant and flame-retardant composite insulation board.
[0014] In a preferred embodiment of the present invention, the epoxy resin is epoxy resin E-51.
[0015] In a preferred embodiment of the present invention, the curing agent is methyltetrahydrophthalic anhydride.
[0016] In a preferred embodiment of the present invention, the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0017] In a preferred embodiment of the present invention, the antioxidant is antioxidant 1010.
[0018] In a preferred embodiment of the present invention, the defoaming agent is BYK-A 535.
[0019] In a preferred embodiment of the present invention, the dispersant is EFKA-4061.
[0020] The beneficial effects of this invention are: This invention discloses a corrosion-resistant and flame-retardant composite insulation board. The process involves uniformly mixing epoxy resin, curing agent, accelerator, acetone, phosphorus-nitrogen-fluorine-silicon compounds, modified hydrotalcite, antioxidant, defoamer, and dispersant in a mixer to obtain a board base material. This base material is then poured into a mold and allowed to stand and cure to obtain the corrosion-resistant and flame-retardant composite insulation board. Using epoxy resin as the main raw material, the addition of phosphorus-nitrogen-fluorine-silicon compounds and modified hydrotalcite forms a flame-retardant network within the composite insulation board, significantly improving its flame-retardant performance and safety. Furthermore, this flame-retardant network exhibits excellent corrosion resistance, making it difficult for corrosive media to penetrate, allowing it to maintain good performance for extended periods in corrosive environments. This significantly enhances the reliability of the composite insulation board, resulting in a composite insulation board that combines excellent mechanical properties, flame-retardant properties, and corrosion resistance, meeting the requirements for long-term use in high-temperature and corrosive environments.
[0021] In the preparation of corrosion-resistant and flame-retardant composite insulation boards, a phosphorus-nitrogen-fluorine-silicon compound was first prepared. This involved the reaction of 2,2-bis(4-aminophenyl)hexafluoropropane, methyl p-formylbenzoate, and DOPO. The amino group on 2,2-bis(4-aminophenyl)hexafluoropropane reacted with the formyl group on methyl p-formylbenzoate to form a Schiff base structure. Subsequently, the PH group on DOPO reacted with the Schiff base structure, introducing the DOPO structure and yielding a DOPO-ester-based fluorinated compound. The ester group on the DOPO-ester-based fluorinated compound underwent hydrolysis to form a carboxyl group, resulting in a DOPO-carboxyl-based fluorinated compound. This compound was then further processed using D... The reaction of DOPO-carboxylated fluorinated compounds with triphenylsilanol results in the introduction of phenyl and silicon atoms into a phosphorus-nitrogen-fluorinated silicon compound. This compound contains a large number of benzene rings, silicon atoms, and fluorine atoms, giving it excellent high-temperature resistance. The presence of phosphorus and nitrogen atoms also contributes to its excellent flame-retardant properties, making the composite insulation board difficult to ignite and easy to self-extinguish after ignition. Furthermore, the presence of silicon and fluorine atoms provides excellent chemical stability, making it difficult to be corroded by corrosive media and significantly improving the corrosion resistance of the composite insulation board.
[0022] In the process of preparing the corrosion-resistant and flame-retardant composite insulation board, a modified hydrotalcite was also prepared. The hydrotalcite was modified using heptadecafluorodecyltriethoxysilane. The siloxane on the heptadecafluorodecyltriethoxysilane hydrolyzes to form silanols, which are then grafted onto the surface of the hydrotalcite. Simultaneously, a large number of fluorine atoms are introduced, resulting in the modified hydrotalcite. The hydrotalcite has a layered structure, which, after modification, allows it to be uniformly dispersed in the composite insulation board. This layered structure creates a "maze effect" within the composite insulation board, significantly extending its lifespan in the presence of corrosive media. The diffusion path is blocked, forming a barrier effect. The presence of fluorine atoms can further enhance its resistance to corrosion media, giving it excellent corrosion resistance. Moreover, the layered structure can also act as a heat insulation barrier, effectively blocking the transfer of heat to the interior of the composite insulation board. Furthermore, the water vapor and carbon dioxide released by its thermal decomposition can dilute the concentration of combustible gases and oxygen in the flame zone, inhibit the combustion chain reaction, and give it excellent flame retardant properties, greatly improving the corrosion resistance and flame retardant properties of the composite insulation board. Detailed Implementation
[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0024] Example 1:
[0025] This embodiment describes a method for preparing a corrosion-resistant and flame-retardant composite insulation board, comprising the following steps: Step S1: 10 mmol of 2,2-bis(4-aminophenyl)hexafluoropropane, 20 mmol of methyl p-formylbenzoate and 70 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 20 °C and 200 r / min for 10 min. The temperature was then raised to 80 °C and the mixture was stirred for 6 h. 20 mmol of DOPO was added and the mixture was stirred for 8 h. After the reaction was completed, the product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into distilled water and vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at 60 °C for 3 h to obtain the DOPO-ester-based fluorinated compound. Step S2: 10 mmol of DOPO-ester fluorinated compound and 20 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred for 20 min at 20 °C and 200 r / min. Then, 30 mL of 1 mol / L potassium hydroxide solution was added and the mixture was heated to 60 °C and stirred for another 20 h. After the reaction was completed, the product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into a 0.03 mol / L hydrochloric acid solution and vacuum filtered. The filter cake was washed twice with distilled water and then placed in a vacuum drying oven and dried at 50 °C for 3 h to obtain DOPO-carboxyl fluorinated compound. Step S3: 10 mmol of DOPO-carboxylated fluorinated compound, 0.8 g of 1-hydroxybenzotriazole and 180 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 20 °C and 200 r / min for 20 min. Then, 10 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 28 mmol of triphenylsilanol were added and the mixture was stirred for another 30 min. The mixture was then heated to 110 °C and stirred for another 20 h. After the reaction was completed, the product was cooled to room temperature and poured into distilled water. The mixture was then vacuum filtered, and the filter cake was washed twice with ethanol. The cake was then placed in a vacuum drying oven and dried at 70 °C for 3 h to obtain a phosphorus-nitrogen-fluorine-silicon compound. Step S4: Add 2g of hydrotalcite with an average particle size of 300 mesh, 1.1g of heptadecafluorodecyltriethoxysilane, 70mL of ethanol and 10mL of deionized water to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 20℃ and 200r / min for 20min. Then adjust the pH to 8.5 with 15% ammonia water. Continue stirring at 70℃ for 4h. After the reaction is complete, cool the reaction product to room temperature and then filter under vacuum. Wash the filter cake twice with distilled water and then place it in a vacuum drying oven and dry at 50℃ for 2h to obtain modified hydrotalcite. Step S5: Weigh out 100 parts by weight of epoxy resin, 80 parts by weight of curing agent, 3 parts by weight of accelerator, 20 parts by weight of acetone, 1 part by weight of phosphorus, nitrogen, fluorine and silicon compound, 7 parts by weight of modified hydrotalcite, 0.7 parts by weight of antioxidant, 0.3 parts by weight of defoamer, and 3 parts by weight of dispersant, and set aside. The epoxy resin is epoxy resin E-51; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the antioxidant is antioxidant 1010; the defoamer is BYK-A 535; and the dispersant is Efka EFKA-4061. Step S6: Add epoxy resin, curing agent, accelerator, acetone, phosphorus, nitrogen, fluorine and silicon compounds, modified hydrotalcite, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step S7: Pour the board base material into the mold, let it stand for 1 hour, then place it in a vacuum drying oven and cure it at 50°C for 1 hour, then raise the temperature to 100°C and cure it for 2 hours, then raise the temperature to 130°C and cure it for 1 hour to obtain a corrosion-resistant and flame-retardant composite insulation board.
[0026] Example 2:
[0027] This embodiment describes a method for preparing a corrosion-resistant and flame-retardant composite insulation board, comprising the following steps: Step S1: 10 mmol of 2,2-bis(4-aminophenyl)hexafluoropropane, 20 mmol of methyl p-formylbenzoate and 75 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 22 °C and 250 r / min for 15 min. The temperature was then raised to 85 °C and the mixture was stirred for 7 h. 20 mmol of DOPO was added and the mixture was stirred for 9 h. After the reaction was completed, the product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into distilled water and vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at 65 °C for 3.5 h to obtain the DOPO-ester-based fluorinated compound. Step S2: 10 mmol of DOPO-ester fluorinated compound and 22 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 22 °C and 250 r / min for 25 min. Then, 32 mL of potassium hydroxide solution with a molar concentration of 1.1 mol / L was added and the mixture was heated to 62 °C and stirred for 22 h. After the reaction was completed, the reaction product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into a hydrochloric acid solution with a molar concentration of 0.04 mol / L and vacuum filtered. The filter cake was washed twice with distilled water and then placed in a vacuum drying oven and dried at 55 °C for 3.5 h to obtain DOPO-carboxyl fluorinated compound. Step S3: 10 mmol of DOPO-carboxylated fluorinated compound, 1 g of 1-hydroxybenzotriazole and 190 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 22 °C and 250 r / min for 25 min. Then, 11 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 29 mmol of triphenylsilanol were added and the mixture was stirred for another 40 min. The mixture was then heated to 115 °C and stirred for another 22 h. After the reaction was completed, the product was cooled to room temperature and poured into distilled water. The mixture was then vacuum filtered, and the filter cake was washed twice with ethanol. The cake was then placed in a vacuum drying oven and dried at 75 °C for 3.5 h to obtain a phosphorus-nitrogen-fluorine-silicon compound. Step S4: Add 2g of hydrotalcite with an average particle size of 300 mesh, 2.4g of heptadecafluorodecyltriethoxysilane, 72mL of ethanol and 11mL of deionized water to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and 250r / min for 25min. Then adjust the pH to 9 with 18% ammonia water. Continue stirring at 75℃ for 5h. After the reaction is complete, cool the reaction product to room temperature and then filter under vacuum. Wash the filter cake twice with distilled water and then place it in a vacuum drying oven and dry at 55℃ for 2.5h to obtain modified hydrotalcite. Step S5: Weigh out 105 parts by weight of epoxy resin, 82 parts by weight of curing agent, 4 parts by weight of accelerator, 21 parts by weight of acetone, 4 parts by weight of phosphorus, nitrogen, fluorine and silicon compound, 11 parts by weight of modified hydrotalcite, 0.8 parts by weight of antioxidant, 0.4 parts by weight of defoamer, and 4.5 parts by weight of dispersant, and set aside for later use; the epoxy resin is epoxy resin E-51; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the antioxidant is antioxidant 1010; the defoamer is BYK-A 535; and the dispersant is Efka EFKA-4061; Step S6: Add epoxy resin, curing agent, accelerator, acetone, phosphorus, nitrogen, fluorine and silicon compounds, modified hydrotalcite, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step S7: Pour the board base material into the mold, let it stand for 1.5 hours, then place it in a vacuum drying oven and cure it at 55°C for 1.5 hours, then raise the temperature to 105°C and cure it for 2.5 hours, then raise the temperature to 135°C and cure it for 1.5 hours to obtain a corrosion-resistant and flame-retardant composite insulation board.
[0028] Example 3:
[0029] This embodiment describes a method for preparing a corrosion-resistant and flame-retardant composite insulation board, comprising the following steps: Step S1: 10 mmol of 2,2-bis(4-aminophenyl)hexafluoropropane, 20 mmol of methyl p-formylbenzoate and 80 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 20 min. The temperature was then raised to 90 °C and the mixture was stirred for 8 h. 20 mmol of DOPO was added and the mixture was stirred for 10 h. After the reaction was completed, the product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into distilled water and vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at 70 °C for 4 h to obtain the DOPO-ester-based fluorinated compound. Step S2: 10 mmol of DOPO-ester fluorinated compound and 25 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 30 min. Then, 35 mL of potassium hydroxide solution with a molar concentration of 1.2 mol / L was added and the mixture was heated to 65 °C and stirred for another 25 h. After the reaction was completed, the reaction product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into a hydrochloric acid solution with a molar concentration of 0.05 mol / L and vacuum filtered. The filter cake was washed three times with distilled water and then placed in a vacuum drying oven and dried at 60 °C for 4 h to obtain DOPO-carboxyl fluorinated compound. Step S3: 10 mmol of DOPO-carboxylated fluorinated compound, 1.2 g of 1-hydroxybenzotriazole and 200 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 25 °C and 300 r / min for 30 min. Then, 12 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 30 mmol of triphenylsilanol were added and the mixture was stirred for another 50 min. The mixture was then heated to 120 °C and stirred for another 25 h. After the reaction was completed, the product was cooled to room temperature and poured into distilled water. The mixture was then vacuum filtered, and the filter cake was washed three times with ethanol. The cake was then placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a phosphorus-nitrogen-fluorine-silicon compound. Step S4: Add 2g of hydrotalcite with an average particle size of 300 mesh, 3.7g of heptadecafluorodecyltriethoxysilane, 75mL of ethanol and 12mL of deionized water to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 300r / min for 30min. Then adjust the pH to 9.5 with 20% ammonia water. Continue stirring at 80℃ for 6h. After the reaction is complete, cool the reaction product to room temperature and then filter under vacuum. Wash the filter cake three times with distilled water and then place it in a vacuum drying oven and dry at 60℃ for 3h to obtain modified hydrotalcite. Step S5: Weigh out 110 parts by weight of epoxy resin, 85 parts by weight of curing agent, 5 parts by weight of accelerator, 22 parts by weight of acetone, 7 parts by weight of phosphorus, nitrogen, fluorine and silicon compound, 15 parts by weight of modified hydrotalcite, 0.9 parts by weight of antioxidant, 0.5 parts by weight of defoamer, and 6 parts by weight of dispersant, and set aside for later use; the epoxy resin is epoxy resin E-51; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the antioxidant is antioxidant 1010; the defoamer is BYK-A 535; and the dispersant is Efka EFKA-4061; Step S6: Add epoxy resin, curing agent, accelerator, acetone, phosphorus, nitrogen, fluorine and silicon compounds, modified hydrotalcite, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step S7: Pour the board base material into the mold, let it stand for 2 hours, then place it in a vacuum drying oven and cure it at 60°C for 2 hours, then raise the temperature to 110°C and cure it for 3 hours, then raise the temperature to 140°C and cure it for 2 hours to obtain a corrosion-resistant and flame-retardant composite insulation board.
[0030] Comparative Example 1: This comparative example illustrates a method for preparing a corrosion-resistant and flame-retardant composite insulation board, comprising the following steps: Step S1: Weigh out 110 parts by weight of epoxy resin, 85 parts by weight of curing agent, 5 parts by weight of accelerator, 22 parts by weight of acetone, 0.9 parts by weight of antioxidant, 0.5 parts by weight of defoamer, and 6 parts by weight of dispersant, and set aside. The epoxy resin is epoxy resin E-51; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the antioxidant is antioxidant 1010; the defoamer is BYK-A 535; and the dispersant is Efka EFKA-4061. Step S2: Add epoxy resin, curing agent, accelerator, acetone, antioxidant, defoamer and dispersant to a mixer and mix evenly to obtain the board base material; Step S3: Pour the board base material into the mold, let it stand for 2 hours, then place it in a vacuum drying oven and cure it at 60°C for 2 hours, then raise the temperature to 110°C and cure it for 3 hours, then raise the temperature to 140°C and cure it for 2 hours to obtain a corrosion-resistant and flame-retardant composite insulation board.
[0031] Comparative Example 2: This comparative example illustrates a method for preparing a corrosion-resistant and flame-retardant composite insulation board, comprising the following steps: Step S1: 10 mmol of 2,2-bis(4-aminophenyl)hexafluoropropane, 20 mmol of methyl p-formylbenzoate and 80 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 20 min. The temperature was then raised to 90 °C and the mixture was stirred for 8 h. 20 mmol of DOPO was added and the mixture was stirred for 10 h. After the reaction was completed, the product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into distilled water and vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at 70 °C for 4 h to obtain the DOPO-ester-based fluorinated compound. Step S2: 10 mmol of DOPO-ester fluorinated compound and 25 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25 °C and 300 r / min for 30 min. Then, 35 mL of potassium hydroxide solution with a molar concentration of 1.2 mol / L was added and the mixture was heated to 65 °C and stirred for another 25 h. After the reaction was completed, the reaction product was cooled to room temperature and the solvent was removed by rotary evaporation. The product was then poured into a hydrochloric acid solution with a molar concentration of 0.05 mol / L and vacuum filtered. The filter cake was washed three times with distilled water and then placed in a vacuum drying oven and dried at 60 °C for 4 h to obtain DOPO-carboxyl fluorinated compound. Step S3: 10 mmol of DOPO-carboxylated fluorinated compound, 1.2 g of 1-hydroxybenzotriazole and 200 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 25 °C and 300 r / min for 30 min. Then, 12 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 30 mmol of triphenylsilanol were added and the mixture was stirred for another 50 min. The mixture was then heated to 120 °C and stirred for another 25 h. After the reaction was completed, the product was cooled to room temperature and poured into distilled water. The mixture was then vacuum filtered, and the filter cake was washed three times with ethanol. The cake was then placed in a vacuum drying oven and dried at 80 °C for 4 h to obtain a phosphorus-nitrogen-fluorine-silicon compound. Step S4: Weigh out 110 parts by weight of epoxy resin, 85 parts by weight of curing agent, 5 parts by weight of accelerator, 22 parts by weight of acetone, 7 parts by weight of phosphorus, nitrogen, fluorine and silicon compound, 0.9 parts by weight of antioxidant, 0.5 parts by weight of defoamer and 6 parts by weight of dispersant, and set aside; the epoxy resin is epoxy resin E-51; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the antioxidant is antioxidant 1010; the defoamer is BYK-A 535; and the dispersant is Efka EFKA-4061; Step S5: Add epoxy resin, curing agent, accelerator, acetone, phosphorus, nitrogen, fluorine and silicon compounds, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step S6: Pour the board base material into the mold, let it stand for 2 hours, then place it in a vacuum drying oven and cure it at 60°C for 2 hours, then raise the temperature to 110°C and cure it for 3 hours, then raise the temperature to 140°C and cure it for 2 hours to obtain a corrosion-resistant and flame-retardant composite insulation board.
[0032] Comparative Example 3: This comparative example illustrates a method for preparing a corrosion-resistant and flame-retardant composite insulation board, comprising the following steps: Step S1: 2g of hydrotalcite with an average particle size of 300 mesh, 3.7g of heptadecafluorodecyltriethoxysilane, 75mL of ethanol and 12mL of deionized water were added to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 25℃ and 300r / min for 30min. Then the pH was adjusted to 9.5 with 20% ammonia water. The mixture was then heated to 80℃ and stirred for 6h. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The filter cake was washed three times with distilled water and then placed in a vacuum drying oven and dried at 60℃ for 3h to obtain modified hydrotalcite. Step S2: Weigh out 110 parts by weight of epoxy resin, 85 parts by weight of curing agent, 5 parts by weight of accelerator, 22 parts by weight of acetone, 15 parts by weight of modified hydrotalcite, 0.9 parts by weight of antioxidant, 0.5 parts by weight of defoamer, and 6 parts by weight of dispersant, and set aside. The epoxy resin is epoxy resin E-51; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the antioxidant is antioxidant 1010; the defoamer is BYK-A 535; and the dispersant is Efka EFKA-4061. Step S3: Add epoxy resin, curing agent, accelerator, acetone, modified hydrotalcite, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step S4: Pour the board base material into the mold, let it stand for 2 hours, then place it in a vacuum drying oven and cure it at 60°C for 2 hours, then raise the temperature to 110°C and cure it for 3 hours, then raise the temperature to 140°C and cure it for 2 hours to obtain a corrosion-resistant and flame-retardant composite insulation board.
[0033] Comparative Example 4: This comparative example illustrates a method for preparing a corrosion-resistant and flame-retardant composite insulation board, comprising the following steps: Step S1: Weigh out 110 parts by weight of epoxy resin, 85 parts by weight of curing agent, 5 parts by weight of accelerator, 22 parts by weight of DOPO, 15 parts by weight of hydrotalcite, 0.9 parts by weight of antioxidant, 0.5 parts by weight of defoamer, and 6 parts by weight of dispersant, and set aside. The epoxy resin is epoxy resin E-51; the curing agent is methyltetrahydrophthalic anhydride; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the average particle size of the hydrotalcite is 300 mesh; the antioxidant is antioxidant 1010; the defoamer is BYK-A 535; and the dispersant is Efka EFKA-4061. Step S2: Add epoxy resin, curing agent, accelerator, acetone, DOPO, hydrotalcite, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step S3: Pour the board base material into the mold, let it stand for 2 hours, then place it in a vacuum drying oven and cure it at 60°C for 2 hours, then raise the temperature to 110°C and cure it for 3 hours, then raise the temperature to 140°C and cure it for 2 hours to obtain a corrosion-resistant and flame-retardant composite insulation board.
[0034] The corrosion-resistant and flame-retardant composite insulation boards of Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in the table below:
[0035] Referring to the data in the table above, and based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the composite insulation board has high tensile strength, high tensile strength retention rate after neutral salt spray test, UL 94 rating reaches V-0 level, and high limiting oxygen index. This indicates that the addition of phosphorus, nitrogen, fluorine, and silicon compounds and modified hydrotalcite can significantly improve the corrosion resistance and flame retardant properties of the composite insulation board.
[0036] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0037] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A corrosion-resistant and flame-retardant composite insulation board, characterized in that, Includes the following components by weight: The composition includes 100-110 parts epoxy resin, 80-85 parts curing agent, 3-5 parts accelerator, 20-22 parts acetone, 1-7 parts phosphorus, nitrogen, fluorine and silicon compounds, 7-15 parts modified hydrotalcite, 0.7-0.9 parts antioxidant, 0.3-0.5 parts defoamer, and 3-6 parts dispersant. The phosphorus, nitrogen, fluorine, and silicon compound is prepared by the following steps: Step a1: 2,2-bis(4-aminophenyl)hexafluoropropane, methyl p-formylbenzoate and N,N-dimethylformamide were stirred and reacted. Then DOPO was added and the reaction was stirred and reacted. After the reaction was completed, the reaction product was cooled, then evaporated by rotary evaporation, then poured into distilled water, then filtered under vacuum, and the filter cake was dried to obtain DOPO-ester-fluorinated compound. Step a2: The DOPO-ester-fluorinated compound and tetrahydrofuran were stirred and reacted. Then, potassium hydroxide solution was added and the reaction was continued with stirring. After the reaction was completed, the reaction product was cooled and then evaporated by rotary evaporation. The product was then poured into hydrochloric acid solution and then filtered under vacuum. The filter cake was washed and dried to obtain the DOPO-carboxyl-fluorinated compound. Step a3: DOPO-carboxylated fluorinated compound, 1-hydroxybenzotriazole and dimethyl sulfoxide were stirred and reacted. Then 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and triphenylsilanol were added and the reaction was stirred and reacted. After the reaction was completed, the reaction product was cooled and poured into distilled water. Then vacuum filtered, and the filter cake was washed and dried to obtain phosphorus, nitrogen, fluorine and silicon compound.
2. The corrosion-resistant and flame-retardant composite insulation board according to claim 1, characterized in that, The ratio of 2,2-bis(4-aminophenyl)hexafluoropropane, methyl p-formylbenzoate, N,N-dimethylformamide, and DOPO in step a1 is 10 mmol: 20 mmol: 70-80 mL: 20 mmol.
3. The corrosion-resistant and flame-retardant composite insulation board according to claim 1, characterized in that, The ratio of the DOPO-ester fluorinated compound, tetrahydrofuran, and potassium hydroxide solution used in step a2 is 10 mmol: 20-25 mL: 30-35 mL.
4. The corrosion-resistant and flame-retardant composite insulation board according to claim 1, characterized in that, The molar concentration of the potassium hydroxide solution in step a2 is 1-1.2 mol / L; the molar concentration of the hydrochloric acid solution is 0.03-0.05 mol / L.
5. The corrosion-resistant and flame-retardant composite insulation board according to claim 1, characterized in that, The ratio of the amounts of DOPO-carboxylated fluorinated compound, 1-hydroxybenzotriazole, dimethyl sulfoxide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and triphenylsilanol in step a3 is 10 mmol: 0.8-1.2 g: 180-200 mL: 10-12 mmol: 28-30 mmol.
6. The corrosion-resistant and flame-retardant composite insulation board according to claim 1, characterized in that, The modified hydrotalcite was prepared by the following steps: Hydrotalcite, heptadecafluorodecyltriethoxysilane, ethanol, and deionized water were stirred and reacted. The pH was then adjusted with ammonia, and the reaction was continued with stirring. After the reaction was completed, the reaction product was cooled, then vacuum filtered, and the filter cake was washed and dried to obtain modified hydrotalcite.
7. The corrosion-resistant and flame-retardant composite insulation board according to claim 6, characterized in that, The ratio of hydrotalcite, heptadecafluorodecyltriethoxysilane, ethanol, and deionized water is 2g:1.1-3.7g:70-75mL:10-12mL.
8. The corrosion-resistant and flame-retardant composite insulation board according to claim 6, characterized in that, The average particle size of the hydrotalcite is 300 mesh; the mass fraction of the ammonia water is 15-20%.
9. The corrosion-resistant and flame-retardant composite insulation board according to claim 1, characterized in that, The preparation method of the corrosion-resistant and flame-retardant composite insulation board includes the following steps: Step 1: Weigh out 100-110 parts of epoxy resin, 80-85 parts of curing agent, 3-5 parts of accelerator, 20-22 parts of acetone, 1-7 parts of phosphorus, nitrogen, fluorine and silicon compounds, 7-15 parts of modified hydrotalcite, 0.7-0.9 parts of antioxidant, 0.3-0.5 parts of defoamer and 3-6 parts of dispersant according to the weight ratio, and set aside. Step 2: Add epoxy resin, curing agent, accelerator, acetone, phosphorus, nitrogen, fluorine and silicon compounds, modified hydrotalcite, antioxidant, defoamer and dispersant into a mixer and mix evenly to obtain the board base material; Step 3: Pour the board base material into the mold, let it stand for 1-2 hours, then place it in a vacuum drying oven and cure it at 50-60℃ for 1-2 hours, then raise the temperature to 100-110℃ and cure it for 2-3 hours, then raise the temperature to 130-140℃ and cure it for 1-2 hours to obtain the corrosion-resistant and flame-retardant composite insulation board.
10. The corrosion-resistant and flame-retardant composite insulation board according to claim 9, characterized in that, The epoxy resin is epoxy resin E-51; The curing agent is methyltetrahydrophthalic anhydride; The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; The antioxidant is antioxidant 1010; The defoaming agent is BYK-A 535; The dispersant is EFKA-4061.
